Extending 0-Search and 0-Merge Hypothesis to the Linearization of Syntactic Objects and its Biolinguistic Implication - Gazil, Philip Jade; Bundukin , Rosemarie (International Journal of Language and Literary Studies, 2023)
T0-Search and 0-Merge hypothesis proposed by Kato et al. (2016) and Fukui et al. (2017) attempts to reduce the operations outside the narrow syntax by further reducing Merge into a set of primitive operations. This is only possible if operations such as Agreement, Binding, Chain Formation, and Labeling are expressed as set-theoretic relations. With this premise, we argue that M0S0 hypothesis can be extended to the linearization of syntactic objects (SOs). In particular, we propose that (i) linear order of two SOs when expressed as a set-theoretic relation, {{?}, {?, ?}}, can be captured by M0S0, (ii) Minimality condition on M0S0 (WS) and Structural Prominence can stand in place of Asymmetric C-command Condition adopted by Kayne’s (1994) Linear Correspondence Axiom, (iii) M0S0 only linearizes SOs inside a Current in line with the Multiple Spell-Out model of Uriagereka (2001, 2012), and (iv) this extension of the M0S0 (WS) hypothesis to include linearization has an implication on Chomsky’s theory of evolution of language i.e., linear order may have been a result of exaptation of Internal Merge to another domain—speech.